If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8v + -36 = -2v + 10 Reorder the terms: -36 + -8v = -2v + 10 Reorder the terms: -36 + -8v = 10 + -2v Solving -36 + -8v = 10 + -2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '2v' to each side of the equation. -36 + -8v + 2v = 10 + -2v + 2v Combine like terms: -8v + 2v = -6v -36 + -6v = 10 + -2v + 2v Combine like terms: -2v + 2v = 0 -36 + -6v = 10 + 0 -36 + -6v = 10 Add '36' to each side of the equation. -36 + 36 + -6v = 10 + 36 Combine like terms: -36 + 36 = 0 0 + -6v = 10 + 36 -6v = 10 + 36 Combine like terms: 10 + 36 = 46 -6v = 46 Divide each side by '-6'. v = -7.666666667 Simplifying v = -7.666666667
| 8(s-10)=124 | | 16=x+(x-2)(0.25) | | 5q+3t-2q-2t=0 | | 24=8q | | X-54=5(2x+3)-11 | | 5x+100-60=0 | | 25-x=2x+1 | | 8(x+8)=16-8x | | -2(x-10)=50 | | 3x-10=7x*2 | | 9x+27=345 | | 2(3x+8)=94 | | 4x+2=122 | | h/-26 | | 3x-0=180 | | (5x-8)(7y-1)= | | X-83=9(2x+3)-25 | | f(-4)=-4+11 | | 5t-4t+3t-6t= | | -4(2x-3)-(10x+7)+2=(12x-5)-1 | | 15n/4=21 | | 5x-18=x^2 | | 12.00-1/5 | | 3x+2x+4x=-18 | | -12x+15=22x | | 0.2x=20+10y | | -17x-13=-98 | | (4x-5)(3y-7)= | | 6x-5x^(1/2)=6 | | 225.132/7.3 | | 3x-4=9+5x | | 5z+2-z=14+2 |